The reproductive season of Acropora in Socotra, Yemen - Baird, Andrew H. (F1000Research, 2014)
Determining when corals reproduce has clear management and economic implications. Here we document the reproductive condition of corals in the genus Acropora on the island of Socotra in Yemen during February 2014. Twenty percent of colonies (n = 143) contained mature gametes and 28% had immature gametes indicating that spawning will occur in both February and March in 2014, confirming previous anecdotal reports of coral spawning at this time in Socotra. Acropora typically reproduce in synchrony with many other broadcast spawning scleractinian corals, and we therefore predict that many other species are reproductively active at this time of year.